MicroRNA-1182 and let-7a exert synergistic inhibition on invasion, migration and autophagy of cholangiocarcinoma cells through down-regulation of NUAK1 - Xin Pan; Gang Wang; Baoming Wang (Cancer Cell International, 2021)
Abstract Background Cholangiocarcinoma (CCA) is the second most common primary liver malignancy worldwide. Several microRNAs (miRNAs) have been implicated as potential tumor suppressors in CCA. This study aims to explore the potential effects of miR-1182 and let-7a on CCA development. Methods Bioinformatics analysis was conducted to screen differentially expressed genes in CCA, Western blot analysis detected NUAK1 protein expression and RT-qPCR detected miR-1182, let-7a and NUAK1 expression in CCA tissues and cell lines. Dual luciferase reporter gene assay and RIP were applied to validate the relationship between miR-1182 and NUAK1 as well as between let-7a and NUAK1. Functional experiment was conducted to investigate the role of miR-1182, let-7a and NUAK1 in cell migration, proliferation and autophagy. Then, the CCA cells that received various treatments were implanted to mice to establish animal model, followed by tumor observation and HE staining to evaluate lung metastasis. Results CCA tissues and cells were observed to have a high expression of NUAK1 and poor expression of miR-1182 and let-7a. NUAK1 was indicated as a target gene of miR-1182 and let-7a. Importantly, upregulation of either miR-1182 or let-7a induced autophagy, and inhibited cell progression and in vivo tumor growth and lung metastasis; moreover, combined treatment of miR-1182 and let-7a overexpression presented with enhanced inhibitory effect on NUAK1 expression and CCA progression, but such synergistic effect could be reversed by overexpression of NUAK1. Conclusion Taken together, the findings suggest the presence of a synergistic antitumor effect of miR-1182 and let-7a on the development of CCA via the down-regulation of NUAK1, providing novel insight into the targeted therapy against CCA.